EPIDEMIOLOGICAL ASPECTS OF THE INCIDENCE OF HIV INFECTION IN THE RUSSIAN FEDERATION AND KUZBASS - Андрей Георгиевич Петров; Сергей Николаевич Филимонов; Виктор Андреевич Семенихин; Ольга Владимировна Хорошилова; Ирина Герасимовна Танцерева; Наталья Степановна Черных (Медицина в Кузбассе)
Human immunodeficiency virus (HIV infection) is one of the most severe non-epidemic and socially caused infectious diseases worldwide. HIV infection is an infectious anthroponotic chronic disease caused by the human immunodeficiency virus, slowly progressing and characterized by damage to the immune system with the development of acquired immune deficiency syndrome (AIDS). AIDS is the final stage of HIV infection and was first described by the US Centers for Disease Control and Prevention in 1981, and its causative agent, the human immunodeficiency virus (HIV), was described in the early 1980s. The source of infection is a person infected with HIV in any stages of the disease. The role of an infected person as a source of infection increases in the early and late stages of the disease. The review presents the results of the analysis of morbidity at the Russian, as well as at the regional level. HIV infection of the world's population is considered not only as a medical problem, but also as one of the main social problems.